Numerical Analysis of Progressive Failure of DM Columns beneath Embankment on Soft Ground - Zheng Gang; Diao Yu; Zhou Haizuo (Deep Foundations Institute, 2015)
"The conventional design method for the embankment supported by DM columns usually assumes the simultaneous failure of all the columns. However, the progressive failure may occur in practice, especially considering that many researches have justified the critical load of DM columns is bending moment. In this study, a finite difference method was adopted to simulate the embankment on soft clay improved by DM columns. An increasing surcharge was applied on the embankment surface to investigate the mechanism of the progressive failure of columns beneath embankment. To capture the brittle bending failure of the DM columns, the model employed a cut-off method, in which the column was separated on failed section as long as the ultimate bending failure was reached. Furthermore, high-strength DM columns were used to enhance the global stability of embankment in this study. The numerical results showed that the ultimate bending failure was first reached at the column beneath embankment toe, and then a continuous collapse extended to the column beneath the embankment shoulder. It is found that the reinforcement could be obviously effective when the reinforced area of high-strength DM columns was extended to a certain area.INTRODUCTIONDeep mixed (DM) columns have been commonly used as a soil-improvement technique to increase stability and to reduce settlement of embankment. Research on failure modes of DM columns owing to embankment fill and surcharge has been the subject of interest for a number of investigators (Miyake 1991; Kitazume 2000; Han 2005; 2006).The potential failure modes of DM column include bending, inclination, shearing, rotating, soil flowing and a combination of these modes (Kitazume and Terashi 1991; Broms 1999). Many researchers have found that bending failure of DM columns was more critical than the shear failure. A centrifuge test was performed by Kitazume (2000) and the results showed that the columns failed in bending before shear failure. In addition, several numerical computations illustrated that design method using the shear strength overestimated the stability of embankment over DM columns (Han and Huang 2005; 2006; Navin 2006; Liu 2007; Wang 1996). In practice, an equivalent shear strength method based on bending failure could better reflect the stability of embankment (Zheng 2010; China Code JGJ79-2011)."